Theaflavin-3,3′-Digallate Promotes the Formation of Osteoblasts Under Inflammatory Environment and Increases the Bone Mass of Ovariectomized Mice - Ge, Gaoran; Yang, Sen; Hou, Zhenyang; Gan, Minfeng; Tao, Huaqiang; Zhang, Wei; Li, Wenming; Wang, Zheng; Hao, Yuefeng; Gu, Ye; Geng, Dechun (Frontiers in Pharmacology, 2021)
Postmenopausal osteoporosis is a disease of bone mass reduction and structural changes due to estrogen deficiency, which can eventually lead to increased pain and fracture risk. Chronic inflammatory microenvironment leading to the decreased activation of osteoblasts and inhibition of bone formation is an important pathological factor that leads to osteoporosis. Theaflavin-3,3’-digallate (TFDG) is an extract of black tea, which has potential anti-inflammatory and antiviral effects. In our study, we found that TFDG significantly increased the bone mass of ovariectomized (OVX) mice by micro-CT analysis. Compared with OVX mice, TFDG reduced the release of proinflammatory cytokines and increase the expression of osteogenic markers in vivo. In vitro experiments demonstrated that TFDG could promote the formation of osteoblasts in inflammatory environment and enhance their mineralization ability. In this process, TFDG activated MAPK, Wnt/β-Catenin and BMP/Smad signaling pathways inhibited by TNF-α, and then promoted the transcription of osteogenic related factors including Runx2 and Osterix, promoting the differentiation and maturation of osteoblasts eventually. In general, our study confirmed that TFDG was able to promote osteoblast differentiation under inflammatory environment, enhance its mineralization ability, and ultimately increase bone mass in ovariectomized mice. These results suggested that TFDG might have the potential to be a more effective treatment of postmenopausal osteoporosis.